Church legal persons conducting charity and care activities as an entity of the social economy - Poniatowski, Michał (Prawo Kanoniczne, 2024)
The article contains an analysis of the current issue of church legal persons conducting charity and care activities as an entity of the social economy. The legal argument begins with an analysis of the legal definition of a social economy entity and the possible legal inclusion of the distinctiveness of charitable activities conducted by church legal entities. The rest of the article concerns the status of a social enterprise in the context of the conditions for obtaining it. The article also contains an analysis of statutory instruments supporting social economy entities as well as the scope of support for social economy entities by public administration bodies. The conclusions of this analysis are included in the conclusion.